Specific features of accumulation of heavy metals in the body of mollusks (Molluska: Limacidae) of the southern slope of the Aragats mountain range - V. S. Hovhannisyan; L. D. Arutyunova; L. S. Mirumyan; M. Z. Magomedova; P. D. Magomedova; T. E. Poghosyan (Юг России: экология, развитие)
Aim. The aim of this work is the study of the specifics of accumulation of heavy metals in the body of gastropod mollusks ‐ slugs (Molluska: Limacidae) on the southern slope of the Aragats mountain range, namely, conducting a quantitative analysis of heavy metals in the soil of different points of the Aragats mountain range and in the body of slugs (Vitrinoides monticola armeniaca; Deroceras caucasicum; Limax flavus), as well as the principles of biogenic migration of heavy metals according to the soil– plant–animal system (slugs) and determining the role of slugs in this migration in terrestrial ecosystems.Material and Methods. Slugs collected from different points of the southern slope of the Aragats mountain range served as material for this study. The content of heavy metals (Cu, Zn, Pb, Ca, Mo) in the body of the mollusks was determined by the Atomic Absorption Spectrophotometry method: AAS extraction & ISO‐8288. The features of the biological accumulation of heavy metals in the body of mollusks were also determined.Results. Gastropod mollusks (Molluska: Limacidae) actively accumulate heavy metals (especially Cu, Zn, Ca) in their bodies and play a certain role in their transfer through food chains. Slugs, living in upper soil horizons (mesofauna) and under stones and plant litter, actively respond to the slightest changes in the environment and are perspective objects allowing the detection of deviations in the functioning of soils and the natural complex as a whole.Conclusion. Slugs living in the soil are an important link of the biogenic migration of heavy metals. An inverse relationship was revealed between the total and removable number of heavy metals in migration through the system: soil–plant–organism.